Atlas of Global Development: A Visual Guide to the World's Greatest Challenges - WorldBank (World Bank, 2015)
COMPLETELY REVISED AND UPDATED Published in association with Harper Collins, the completely revised and updated fourth edition of the Atlas of Global Development is a comprehensive guide to the most critical issues facing our changing world today.